Exploring the emergence of vertical transmission of SARS-CoV-2: A Rapid Review: Exploring the emergence of vertical transmission of SARS-CoV-2: - Jain, Vidhi; Kanchan, Tanuj; Krishan, Kewal (Acta Biomedica Atenei Parmensis, 2020)
Novel Coronavirus, SARS-CoV-2 is responsible for the global pandemic of COVID-19. It has been shown to spread through respiratory droplets, direct contact and environmental fomites. The possibility of its spread by other modes viz. airborne, fecal-oral, vertical, etc. is being explored and can have implications in planning preventive strategies and disease management. A systematic analysis was carried out using the keywords; “COVID 19 vertical transmission”, “SARS-CoV-2 pregnancy”, and “SARS-CoV-2 vertical transmission”, and the cases suggestive of possible vertical transmission of SARS-CoV-2 were studied in detail. The available evidences point at a possibility of vertical transmission of SARS-CoV-2.